Dose-Response Relationships in Human Experimental Exposure to Solvents - Ivo Iavicoli; Giovanni Carelli; Alessandro Marinaccio (SAGE Publishing, 2006)
Previous studies carried out in the field of experimental toxicology have shown evidence of biphasic dose-response relationships for different experimental models, end-points and chemicals tested. As these studies excluded humans as the experimental model, we have examined the literature of the last three decades in order to verify data concerning human experimental exposure with the aim of highlighting possible biphasic dose-response relationships. The substances used for experimental exposures included hydrocarbons, esters, alcohols, ketones, ethers, glycoethers, halogenated hydrocarbons, and carbon sulphide; the absorption route was inhalation. We did not detect any biphasic dose-response relationship and, in the studies reviewed, our examination revealed major methodological limitations that prevented us making a more detailed examination of experimental data. We concluded that the experimental data available did not allow us to support evidence of biphasic dose-response relationships in human experimental exposure to the above-mentioned chemical substances.